Mechanism study of the impact of water-borne bacteria on flotation - Liu, W.; Moran, Chris; Vink, S. (Elsevier, 2013)
Bacteria-containing water is being increasingly accessed by the minerals industry as an alternative water source to improve water efficiency. Water-borne bacteria have been shown to negatively affect the efficiency of froth flotation when using a representative system consisting of E. coli as the model bacterium and chalcopyrite as the model mineral. It is essential to understand the underlying mechanisms that could explain the observed effect, to provide guidance on the subsequent solutions to deal with it. This study conducted a systematic investigation into the mechanism by which bacteria affect flotation efficiency using fluorescence microscopy, bubble attachment time measurements, and froth phase characteristics. E. coli bacterial cells in solution were found to attach to chalcopyrite surfaces. In turn, the surface hydrophobicity of chalcopyrite particles decreased as the number of the attached bacterial cells increased. Reduction in surface hydrophobicity resulted in less mineral particles attaching to bubbles, leading to decreased froth stability, bubble coalescence rate and froth velocity. Slurry pH and Eh were also affected by the presence of the bacterial cells. These changes were correlated with reductions in flotation recoveries. These experimental results contribute to an understanding of how biotic water constituents impact the operation of flotation plants that choose to use alternative water sources, and provide knowledge towards possible solutions to the negative effect of water-borne bacteria. © 2013 Elsevier Ltd.